Peran Pendidikan Agama Kristen Di Era Digital Sebagai Upaya Mengatasi Penggunaan Gadget Yang Berlebihan Pada Anak Dalam Keluarga Di Era Disrupsi 4.0 - Fredik Melkias Boiliu (Sekolah Tinggi Teologi Real Batam, 2020)
This article reviews the teaching of Christian religious education in the digital age as an effort to overcome the excessive use of gadgets in children in families in the era of disruption 4.0. Technological advances are so fast and increasingly sophisticated bring major changes in human life in various fields. In this case, such a gadged can have a big impact and everyone in the world must have been connected with the gadget. The use of gadgets is not for people who work, but almost all people, including children and toddlers, are already using gadgets in their daily activities. Gadgets have good values and benefits for certain people, but many negative impacts arise in the excessive use of gadgets for teenagers, children, and even toddlers. Therefore, parents have a very important role to overcome the excessive use of gadgets in children through the teaching of Christian religious education in the family. In carrying out Christian religious education in the family, parents play a role as teachers, educators and assistants to children in the use of gadgets. The method used in this paper is literature review and library research.